Repensando o ciclo: avaliação do ciclo de vida do ácido polilático em substituição do polietileno em absorventes descartáveis - Pereira, Beatriz Aparecida Muniz (Universidade Federal de São Carlos, 2020)
The strong trend of products with more sustainable life cycles is promoting changes in the way they are produced today, with the search for cleaner energy matrices, renewable sources, and environmentally favorable waste treatments. The Life Cycle Assessment (LCA) tool aims to quantify the direct and indirect environmental impacts of these products and services, throughout their entire life cycle, from the extraction of raw materials to their final disposal. Although the use of the method started in 1960, its application has become widespread today. A product that has a very controversial life cycle is the conventional polymer, as it has a fossil origin and is not biodegradable. Therefore, alternatives are sought for its application, such as biopolymers, for example. Biopolymers are defined as polymers originating from renewables raw materials and which have a shorter life cycle. Among them stands out the polylactic acid (PLA), which originates from starch or sugar and can be used in several applications, among them the disposable sanitary pad. The work brought a comparison between the life cycle impacts of the PE sanitary pad and the PLA sanitary pad. The results showed the PLA sanitary pad has the most sustainable process. PE sanitary pad has more negative impacts on the environment in relation to global warming, abiotic depletion of fossil fuels, human toxicity, marine ecotoxicity, freshwater ecotoxicity and photochemical oxidation. However, the results showed that PLA sanitary pad also has significant negative impacts on its life cycle that must be carefully evaluated, such as abiotic mineral depletion, acidification, eutrophication, ozone layer depletion and terrestrial ecotoxicity. In addition of these results, the work also presented the LCA method as a useful tool for the development a sustainable chemical industry.
Rethinking the cycle: evaluation of the life cycle of polylactic acid replacing polyethylene in sanitary pads
Keywords: Avaliação de Ciclo de Vida; Sustentabilidade; Ácido polilático; Absorventes descartáveis; Life Cycle Assessment; Sustainability; Polylactic acid; Sanitary pads; ENGENHARIAS::ENGENHARIA QUIMICA